Hitra izdelava prototipov - Kopač, Janez (Strojniški vestnik, 2000)
Industry requires shorter times to launch products on to the market. It also demand s product variety, lower prices and other product improvements. As a consequence of these demands Rapid Prototyping (RP) has been developed.It is now possible to produce, test and investigate prototypes more rapidly than ever, which helps in time shortening for new product development. Products made by RP have accuracy and quality of the surface as good as parts made by cutting (turning, milling, etc). This paper describes and compares the benefits and differences between conventional and various RP methods of product development.
Keywords: izdelava prototipov hitra; rapid prototyping; tehnologije izdelave; modeliranje; prototipi; orodja; izdelava